Behavioural synchronization of large‐scale animal movements – disperse alone, but migrate together?. (6th May 2016) - Cote, Julien; Bocedi, Greta; Debeffe, Lucie; Chudzińska, Magda E.; Weigang, Helene C.; Dytham, Calvin; Gonzalez, Georges; Matthysen, Erik; Travis, Justin; Baguette, Michel; Hewison, A. J. Mark
ABSTRACT: Dispersal and migration are superficially similar large‐scale movements, but which appear to differ in terms of inter‐individual behavioural synchronization. Seasonal migration is a striking example of coordinated behaviour, enabling animal populations to track spatio‐temporal variation in ecological conditions. By contrast, for dispersal, while social context may influence an individual's emigration and settlement decisions, transience is believed to be mostly a solitary behaviour. Here, we review differences in drivers that may explain why migration appears to be more synchronized than dispersal. We derive the prediction that the contrast in the importance of behavioural synchronization between dispersal and migration is linked to differences in the selection pressures that drive their respective evolution. Although documented examples of collective dispersal are rare, this behaviour may be more common than currently believed, with important consequences for eco‐evolutionary dynamics. Crucially, to date, there is little available theory for predicting when we should expect collective dispersal to evolve, and we also lack empirical data to test predictions across species. By reviewing the state of the art in research on migration and collective movements, we identify how we can harness these advances, both in terms of theory and data collection, to broaden our understanding of synchronized dispersal and its importance in the context of global change.